The Effect of Islamic Marketing on Customer Loyalty Mediated by Customer Satisfaction a Study of Chicken Slaughterhouses - Muhammad Amar Abiyoso; Muhammad Sholahuddin (Majapahit Journal of Islamic Finance and Management, 2025)
The growing awareness among Muslim consumers regarding the significance of halal and ethical standards in food has prompted businesses, including poultry slaughterhouses, to integrate sharia-compliant principles into their marketing practices. This research investigates the influence of Islamic marketing on customer loyalty, considering customer satisfaction as a mediating factor. Employing a quantitative method, data were gathered from 155 purposively selected consumers in Surakarta who had purchased from chicken slaughterhouses. A structured questionnaire using a Likert Scale was utilized, and data were analyzed through the SEM-PLS technique. Findings reveal that while Islamic marketing exerts a positive yet statistically insignificant impact on customer loyalty, it significantly enhances customer satisfaction. Moreover, customer satisfaction positively and significantly influences loyalty and acts as a significant mediator between Islamic marketing and loyalty. This study provides theoretical contributions by expanding the scope of Islamic marketing studies in the primary food sector, as well as practical contributions in the form of recommendations for marketing strategies that are in accordance with Islamic values. The social implications are increased awareness of the importance of halal consumption and encouragement for local business actors to consistently implement business practices that are in accordance with sharia principles.